2011
DOI: 10.1074/jbc.m110.177246
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of Zn2+, Cu2+, Fe3+, and Al3+ on Amyloid-β Stability, Oligomerization, and Aggregation

Abstract: 3؉ also inhibits fibril formation; however, the annular oligomers co-exist in the aggregation pathway. In conclusion, Zn 2؉ , Cu 2؉ , Fe 3؉ , and Al 3؉ adopt distinct folding and aggregation mechanisms to affect A␤, where A␤ destabilization promotes annular protofibril formation. Our study facilitates the understanding of annular A␤ oligomer formation upon metal ion binding. The brain deposition of amyloid plaques composed of A␤2 is the pathological hallmark of AD (1, 2). A␤ is generated from sequential cleava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
148
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(167 citation statements)
references
References 73 publications
(65 reference statements)
18
148
0
1
Order By: Relevance
“…This indicates that the remaining soluble peptide was already fully loaded with Cu(II), and that the aggregation of a soluble A␤-Cu y complex is rate-limiting as observed under equimolar conditions. Recently it has been shown that Cu(II) decreases the hydrophobic exposed protein surfaces of A␤ when added in supraequimolar ratios (43), which may explain the observed increased solubility of the A␤-Cu complex.…”
Section: Cu(ii):a␤ 1-40 Ratiomentioning
confidence: 99%
“…This indicates that the remaining soluble peptide was already fully loaded with Cu(II), and that the aggregation of a soluble A␤-Cu y complex is rate-limiting as observed under equimolar conditions. Recently it has been shown that Cu(II) decreases the hydrophobic exposed protein surfaces of A␤ when added in supraequimolar ratios (43), which may explain the observed increased solubility of the A␤-Cu complex.…”
Section: Cu(ii):a␤ 1-40 Ratiomentioning
confidence: 99%
“…The experimental conditions for Ab 1-42 fibrillization have been described in previous reports. 7 The increase in the intensity of the fluorescence signal of ThT associated with Ab 1-42 fibrillization is depicted in Figure 8(A). The time course for the formation of the fibrils was also observed through continuous monitoring of the changes in the ThT fluorescence intensity at 480 nm over the course of 24 h; this time period is sufficient to allow fibril formation under incubation and stirring conditions.…”
Section: Evaluation Of Ab 1-42 Aggregation By Thioflavin T Fluorescencementioning
confidence: 99%
“…Some reports have demonstrated that the presence of Cu 21 favors fibril formation, 10 while other recent studies suggested that Cu 21 might inhibit Ab 1242 fibril formation. 7 In addition, numerous compounds have been found to reduce Ab 1242 aggregation in vitro. 11,12 However, the usefulness of these compounds as inhibitors of Ab 1242 aggregation remains speculative due to their lack of specificity and/or unknown mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D-penicillamine, a copper chelating molecule, was shown to have an interest for ADtargeted therapy [187,188] since metal ions such as iron or copper are involved in the formation AD pathogenesis due to the binding of APP, their accumulation in the AD brain [177,189,190]. This compound, already used in therapy of other pathologies such as the Wilson's disease affecting the liver, rheumatoidis and lead poisoning was tested as a nanoformulation where it was covalently linked to NPs in vitro and was successfully shown to disaggregate Aβ peptide [191].…”
Section: Therapeutic Strategies Using Nanoparticles In Ndmentioning
confidence: 99%